On the propagation of Lamb waves in a sandwich plate made of compressible materials with finite initial strains - Akbarov, S. D.; Zamanov, A. D.; Agasiyev, E. R. (SPRINGER, 2008)
The propagation of flexural Lamb waves in a prestrained sandwich plate made from compressible highly elastic materials is investigated within the scope of a piecewise homogeneous body model by utilizing TLTEWISB. The mechanical relations of layer materials are described by a harmonic-type potential, and numerical results are obtained for the first and second vibration modes. According to the results, the influence of problem parameters and of the initial stretching strain along the layers on the wave propagation speed is examined. The asymptotic values of the speed are considered in the cases of short and long wavelengths, and the influence of the initial strains on these asymptotic (limit) values are also analyzed.
Keywords: Lamb waves; initial strains; sandwich plate; wave dispersion; compressible material; 3RD-ORDER ELASTIC-CONSTANTS; STRESS-FIELD; SLAB; Mechanics; Materials Science; Polymer Science